Analisis indeks vegetasi pada citra Landsat 8 untuk penentuan perubahan tutupan lahan di Kabupaten Badung, Provinsi Bali - Putu Aryastana; I Gede Yogi Adnyana Puspita Riana; Ilona Dwiyeni Nahak; I Wayan Wartana; Ida Bagus Made Yatana (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
One of the common problems in urban regions is urbanization, urbanization, and industrialization trigger land use change, this land use change urges green land in urban areas to shrink, triggering building density which in the future will lead to new problems such as limited natural resources, congestion, and air pollution, Badung is a regency that is currently being attacked by massive land changes, therefore this research was conducted to compare the level of vegetation density and the area of vegetation density using the Normalized Difference Vegetation Index (NDVI) technique in 2015 and 2021 over Badung Regency. The supervised classification method was used to produce four classes consisting of water, soil, settlement, and vegetation. The results of this study exhibited the land cover decreased between 2015 and 2021 in the vegetation class around 57.26 km2. On the other hand, there is an increase in the land cover class for the settlement, land, and water body categories of 47.38 km2, 4.08 km2, and 5.80 km2, respectively. These results were obtained with an accuracy rate and kappa coefficient is 89.27% and 0.86, respectively. This indicate the classification recult in this study was feasible to use.